(untitled) (Oratio Directa, 2021)
The contemporary phenomenon of bullying has developed into cyberbullying, which includes insulting, humiliating, intimidating, and threatening others through electronic information or documents. Cyberbullying is frequently found on social media, particularly Instagram, and may affect anyone, including Generation Z. This study examines the forms of cyberbullying and their mental-health consequences for Generation Z aged 20-25 in Jakarta. It uses a qualitative descriptive approach informed by phenomenology and routine activity theory. Data were collected through observation, interviews, and a literature review. The findings identify harassment, trickery, denigration, impersonation, and flaming as relevant forms of cyberbullying. Both victims and perpetrators reported consequences including stress, paranoia, insecurity, depression, and temperamental responses. The study emphasizes the importance of responsible oral and written communication on social media and stronger awareness of cyberbullying prevention.